THE ROLE OF MUSCLE GLYCOGEN UNDER LOW ENERGY AVAILABILITY AND ITS IMPACT ON PERFORMANCE IN FUNCTIONAL SPORTS: A SYSTEMATIC REVIEW - Pires, Jackson Gervasio; Moyano, Lucrecia Natalí (Seven Editora, 2026)
Introduction: Low energy availability (LEA) and reduced muscle glycogen are recognized as key determinants of performance and health in athletes practicing functional sports, which are characterized by high training density and mixed metabolic demands. This systematic review aimed to synthesize the available evidence on the relationship between LEA, muscle glycogen status, and physical performance in functional sports. Methods: A systematic review was conducted following PRISMA 2020 guidelines. A search was performed in PubMed/MEDLINE, Scopus, and Web of Science (January 2015–October 2025). Twelve studies involving trained adults were included. Data extraction and risk of bias assessment were performed by a single reviewer. Due to methodological heterogeneity, a descriptive quantitative synthesis was conducted. Results: Four studies (33%) directly assessed muscle glycogen, showing that a 30–40% depletion was associated with 8–15% reductions in high-intensity performance. Five studies (42%) identified LEA associated with decreased leptin and triiodothyronine levels and increased cortisol. Physiological demands in functional sports included oxygen consumption of 85–92% of VO₂max and lactate concentrations exceeding 10–12 mmol/L. Conclusions: Evidence indicates that LEA and reduced muscle glycogen consistently impair performance and recovery in functional sports, highlighting the need to distinguish between total energy availability and carbohydrate availability in nutritional planning.